ASSESSING THE IMPACT OF INTERNATIONAL PARTNERSHIPS AND COLLABORATIONS ON AFGHAN HIGHER EDUCATION - Aref Ansari, Mohammad; Rahmani, Halima (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
This article evaluates the impact of international partnerships and collaborations on Afghan higher education, focusing on their influence on academic quality, research opportunities, and student outcomes. The findings reveal that these partnerships significantly enhance academic standards by introducing global best practices and aligning Afghan programs with international benchmarks. They also expand research opportunities by providing access to funding, advanced facilities, and global academic networks, although challenges in research quality remain. Furthermore, the collaborations improve student outcomes by offering transformative experiences through exchange programs and joint degrees, thereby fostering a global perspective and improving employability. Overall, international partnerships are crucial for the development and global integration of Afghanistan’s higher education system.